Life of Father Taylor, the sailor preacher (The Boston Port and Seaman's Aid Society, 1904)
Introduction.--Genius: Father Taylor. By C.A. Bartol.--Rev. Mr. Taylor. From the New England magazine, 1835.--Father Taylor and oratory. By W. Whitman.--Life of Father Taylor. By G.Haven and T. Russell.--Historical sketch of the Boston Port amd Seamen's Aid Society.--Articles of incorporation.--By-laws.--Officers.